A Decoupled PI Design for a Second-Order Model of a Magnetic Levitation System - Oscar Danilo Montoya Giraldo; Walter Julián Gil-González; Andrés Leonardo Jutinico-Alarcón (Statistics, Optimization & Information Computing, 2025)
This paper presents a decoupled control strategy for stabilizing a second-order magnetic levitation system (MLS) based on a nonlinear feedback linearization approach combined with a proportional-integral (PI) controller. The proposed methodology transforms the nonlinear dynamics of the MLS into an equivalent linear system using an exact feedback linearization scheme, enabling the application of classical control techniques. Stability of the closed-loop system is formally demonstrated through a Lyapunov-based analysis, ensuring asymptotic convergence to the equilibrium point. The controller structure permits flexible tuning of gains to shape the system’s dynamic response, achieving both critically damped and underdamped behaviors. The performance of the control scheme is validated through extensive numerical simulations under varying gain configurations, demonstrating fast convergence and high precision in position tracking. While the study assumes ideal conditions, the findings provide a foundation for future developments that address robustness against model uncertainties, disturbances, and practical implementation constraints. Overall, this work contributes a theoretically grounded and computationally efficient control design for MLS applications.